The impact of the Ukrainian food crisis on the globalized world - Lytovchenko Artem (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The article is devoted to an overview of the main effects of the food crisis in Ukraine, caused by the Russian invasion, in relation to the world situation in the food sector. The author gives a systemic outline of the macro-level impact of Russia’s war against Ukraine on the problems of hunger, access to healthy food, prospects for destabilization processes in the sphere of food production and supply. The most significant aspects of the influence of hostilities on the production of agricultural products in Ukraine and on its export are considered. We are analyzing the consequences in the field of global pricing on food markets, the global fight against hunger in different countries. The global food crisis, which began long before the Russian invasion, has turned into a lever of global political struggle. Despite the partial leveling of processes in the field of global food security in 2023, it is not yet possible to talk about a return to the indicators of the beginning of 2022. We highlight the general aspects of the operation of the Black Sea Grain Initiative and the consequences of the disruption of its operation are considered. The author notes the ambiguity of the case with the Black Sea Grain Initiative; this ambiguity is illustrated by the position of five Eastern European countries, at whose request the European Commission limited the sale of Ukrainian grain on their territories. The dependence of the global situation in the field of food security on political intrigues and nuances further complicates the process of overcoming food problems. This case causes reputational damage to Ukraine in addition to the direct damage caused by the Russian invasion. It records the growth of crisis processes in the fields related to the food sphere and the ambiguity of the positions of individual European states regarding the crisis of Ukrainian grain exports. We made a conclusion about the large-scale damage caused to the stability of the world food market by direct and indirect consequences of the war in Ukraine, and about the negative prospects of this problematic field.